Exploring Social Skills Development and Their Impact on Students’ Belongingness Needs at the Secondary Level: https://doi.org/10.55966/assaj.2025.4.1.0111 - Naseem Arshad*; Dr. Qaisara Parveen; Prof. Dr. M. Imran Yousuf; Dr. Majid Ali (`, 2025)
This study explored the development of social skills and the sense of belonging among secondary school students in Rawalpindi, Pakistan. Social skills, including communication, cooperation, empathy, conflict resolution, and peer interaction, were considered essential in shaping students’ emotional experiences and relationships within the school environment. The research aimed to examine how these skills influence students’ feelings of acceptance, inclusion, and connectedness, which are vital for their personal development and academic involvement. A quantitative correlational research design was used. A sample of 400 students from 24 public secondary schools in Rawalpindi was selected using proportionate stratified random sampling. Data were gathered through a structured questionnaire adapted from the Social Skills Improvement System (SSIS) and the School Belongingness Scale (SBS). Instrument validity was confirmed by expert review and a pilot study, while reliability was measured using Cronbach’s Alpha, which gave a score of 0.722. Descriptive statistics and cross-tabulation identified subgroup differences. Pearson’s correlation showed a significant positive link between social skills and belonging. Gender, environment, culture, and school climate influenced outcomes. Findings support promoting social-emotional learning to foster belonging and student growth. Keywords: Social skills development, sense of belonging, secondary school students, communication, school climate, emotional well-being, student inclusion, Rawalpindi